The stewardship of wealth successful private wealth management for investors and their advisors - Curtis, Gregory, 1947-; ProQuest (Firm) (Hoboken, N.J. : Wiley, 2013)
"Indispensable advice for building a lasting financial legacyBuilding wealth is hard to do, but maintaining that wealth across generations is even more challenging. In The Stewardship of Wealth: Successful Private Wealth Management for Investors and Their Advisors + Website, wealth advice expert Gregory Curtis reveals the investment secrets of the world's wealthiest families, so that financial planners, fund managers, and wealthy individuals everywhere can follow in their footsteps. Outlining the best practices for preserving and growing wealth, the book details exactly how to build a lasting financial legacy in the face of taxes, inflation, investment costs, and the conflicts of interest that are endemic to the financial advisory business.Wealthy families are at the very heart of America's exceptionalism, of the vigor, resilience, and creativity that have made the U.S. the most successful nation in history. The Stewardship of Wealth's discusses the crucial role private wealth continues to play in America's remarkable economic and cultural success and the issues wealthy families and their advisors face, presenting a step-by-step guide to better managing liquid wealth. Reveals the wealth management strategies employed by America's wealthiest families and their financial managers Explores the challenges to ensuring that money stays in the family, from portfolio design to manager selection to monitoring investment performance, and much more Details the essential steps for ensuring a lasting financial legacy An examination of the key issues involved in managing private wealth, especially for affluent families, The Stewardship of Wealth + Website is the ultimate guide to building a financial legacy that will last"--
pt. 1. The importance of private capital -- pt. 2. The stewardship of wealth -- pt. 3. The rich get richer.
"This book is an updated and expanded edition of Creative Capital: Managing Private Wealth in a Complex World, by Gregory Curtis, copyright 2004 by Gregory Curtis, New York: iUniverse, Inc."--Title page verso.
Includes index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Investments -- United States; Wealth -- United States; Finance -- United States; Electronic books